THE ROLE OF PARENTS IN THE FORMATION OF CHILDREN'S CHARACTER ACCORDING TO AN ISLAMIC PERSPECTIVE WITH A CASE STUDY AT SD PLUS AL-ISHLAH BONDOWOSO - Rahman, Yudi Ardian (Tsaqofah : Jurnal Pendidikan Islam, 2023)
The world of education is considered a stagnant world that only takes care of levels and qualities that can ultimately become capital to find a life based on a materialistic and mechanical mindset. How ironic that education only moves mechanically. As a result, the world of education today is a rigid world and only gives birth to mechanical robots that are not cultured, moral, and only concerned with quality values without paying attention to the qualities that should be most important to form smart humans physically and mentally so that they can form a civilized life of the nation and state. Keywords: Parents' Role, Children's Character Building, Islamic Perspective